The effect of provision of pain management advice on patient satisfaction with their pain management: a pilot, randomised, controlled trial (pain advice trial). Issue 7 (7th March 2016) - Taylor, David McD; Grover Johnson, Olivia; Lee, Marina; Ding, Juen Li; Ashok, Aadith
Abstract : Objective: We aimed to provide pain advice ('The treatment of pain is very important and be sure to tell the staff when you have pain') as an intervention and evaluate its effect upon patient satisfaction. The purpose of this pilot trial was to ensure the design and methods of a future trial are sound, practicable and feasible. Method: We undertook a pilot, randomised, controlled, clinical intervention trial in a single ED. The control arm received standard care. The intervention arm received standard care plus pain advice from an independent investigator. All patients and treating ED staff were blinded to patient enrolment. Patient satisfaction with their pain management (six-point ordinal scale) was measured 48 h post-ED discharge, by a blinded researcher. The primary outcome was satisfaction with pain management. Results: Of the 280 and 275 patients randomised to the control and intervention arms, respectively, 196 and 215 had complete data, respectively. 77.6% (152/196) and 88.8% (191/215) of patients reported being provided with pain advice, respectively (difference 11.3% (95% CI 3.6 to 19.0)). The intervention was associated with absolute and relative increases in patient satisfaction of 6.3% and 14.2%, respectively. 91.3% (179/196) and 76.3% (164/215) of patients who were/were not very satisfied reported having received 'pain advice' (difference 15.0% (95% CI 7.6 to 22.5)). Conclusions: The intervention to provide pain advice resulted in a non-significant increase in patient satisfaction. A larger multicentre trial is feasible and is recommended to further explore the effects of provision of pain advice. Trial registration number: ACTRN12615000097549.